Student practices in use of lecture recordings in two first-year courses: Pointers for teaching and learning - Frith, V.; Lloyd, P. (South African Journal of Higher Education, 2020)
Although there is a large body of research that exists internationally about how students use lecture recordings, it is necessary to consider the South African situation, where a large proportion of students entering higher education are underprepared and for whom English is not their first language. This study investigated student use of lecture recordings in two different first-year courses, one a standard mathematics course and the other a quantitative literacy course using a lecture-workshop mode of delivery. The results from this study confirm much of what has been seen internationally, that is, that students value the availability of lecture recordings and perceive that their learning is improved by having access to them. Lecture recordings are used mainly to make up for missed lectures, but also to review material from lectures and improve notes made in lectures. There is also evidence of increased usage of recordings immediately prior to assessments. This study found no evidence of a relationship between lecture attendance and recording usage. It also revealed that the extent of use of lecture recordings differs in different course contexts, and that students with lower academic English competence make significantly greater use of the recordings. Limitations that became apparent due to reliability of data obtained by different methods (from questionnaires and from the learning management system) are discussed. Finally, recommendations are made for classroom practice that could enhance academically immature students’ use of lecture recordings as a valuable learning resource.